The Effect of Grit on Career Adaptability of Chinese College Students Based on the Self-Regulatory Processes - Li, Haihong; Yu, Xuan; Mei, Yuanfei; Liu, Xuhong; Li, Ling; Luo, Nan (Frontiers in Psychology, 2021)
Intelligence is innate, but grit is something everyone can develop. Grit not only enables students to stick to their goals, but also to persevere even when they fail. Career adaptability is an important concept in vocational education of college students, which is a person engaged in some work, must have a certain physical and psychological quality. Base on the self-regulation theory, this study investigated the relationship between grit and career adaptability of Chinese college student based on the self-regulatory processes. We surveyed 839 Chinese college students and tested a self-regulation model. As expected, grit was related to greater career adaptability via greater career exploration and decision self-efficacy, positive affect and goal commitment. These findings not only broaden the theoretical framework for the effect of grit on career adaptability, but also open up a new horizon for improving college students' career adaptability in practice.